“I Don’t Know Whether It’s Priority, or Capacity, or Both”: Implementation Gaps in Employment Policies Targeting People with Disabilities in Kenya and Bangladesh - Shaffa Hameed; Lopita Huq; David J. N. Musendo; Lena Morgon Banks; Joyce Olenja; Tom Shakespeare (Disabilities, 2024)
Disabled people are often excluded from employment, particularly in accessing waged employment. This exclusion persists despite enabling policies and legislature, indicating a need to address gaps in implementation. To improve policy implementation, it is crucial to better understand the gap between policy intention (what was planned) and effect (what happens), including reasons that widen this gap (what explains what happened). This study explores this in the context of Kenya and Bangladesh, drawing on key informant interviews and analysis of policies and programmes related to employment, social protection, and disability. Using the policy triangle framework, we analysed the policy context, process, actors, and content of relevant policies and programmes. The study identified key policy provisions on employment quota, social assistance, job placement services, tax incentives, and training opportunities, all of which were designed to promote employment for disabled people. However, implementation is limited in both countries, for reasons including ambiguity in policies, unavailability of data for monitoring, and lack of transparency among implementers. The data suggest that addressing these aspects would promote accountability among duty-bearers, advocacy power among rights-holders, and ultimately improve implementation and inclusion of disabled people in employment.